Mitos dalam Novel Dawuk: Kisah Kelabu Dari Rumbuk Randu Karya Mahfud Ikhwan : Kajian Semiotika Rolland Barthes - Nur Fitri Awalia; Anshari Anshari; Andi Agussalim Aj (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This study aims to describe the meaning of phrases, sentences, or paragraphs that contain denotative and connotative meanings and myths contained in the analyzed novels. This research is descriptive qualitative. The data of this research are in the form of phrases, senteces, and paragraphs that contain the meaning of denotation, connotation, and myth in the novel. The data source for this research is the novel Dawuk: Kisah Kelabu dari Rumbuk Randu by Mahfud Ikhwan published by Marjin Kiri in 2017. The approach used is the semiotic study of Rolland Barthes. The results of this study indicate that there are six myths in the novel Dawuk: Kisah Kelabu Dari Rumbuk Randu by Mahfud Ikhwan, namely: Disgraceful love and praiseworthy love, physical form is a measure of harmony in relationship, Good parents will give birth to good children, Obedient people religion has good ethics, Physical beauty is an advantage, and Ugly is a curse. The emergence of the myth is the resultof the meaning of denotation as the  fisrt level and the meaning of connotation as the second level.  Keywords: Semiotics, Denotation, Connotation, Myth.